Analisa Pengaruh Variasi Komposisi Bahan Limbah dari Serat Kelapa Muda, Batang Pisang dan Kertas Bekas terhadap Kekuatan Bending Sebagai Papan Komposit - Enda Apriani (Jurnal Engine: Energi, Manufaktur, dan Material, 2017)
The composite is a combination of two or more materials to produce a new material with unique properties compared to the nature of the base material prior to mixing and surface bonding occurs between each constituent material. The purpose of this research is to know the influence of waste material composition from plant fiber, that is young coconut fiber, banana stem, and calendar waste paper to bending strength on composite board by using Epoxy resin wood type. The process of printing the composite board is done in the Laboratory of Integrated Mechanical Engineering University Proklamasi 45 Yogyakarta. The three raw materials that have been crushed and dried, mixed with the breaking time of each 5" and 10" with their respective ingredients composition, namely Young Coconut Fiber: Banana Stem Fiber: Calendar Waste Paper =25:25:50; 25:50:25; 50:25:25 (%). Each treatment was repeated 3 times. Observation was done by calculating raw material composition and time of destruction process against bending strength of composite board which resulted very significant effect on water content, fracture, and flexibility of composite board. Bending strength testing is performed using a robust Universal Testing Machine (UTM). The result of this research produced the most optimum material composition of bending strength into composite board, ie composition III with the duration of destruction for 5", that is the average MoE value of 17.069,76 kg/cm² and the average value of MoR is 83,78 kg/cm². From this research is expected to get new engineering technique from agriculture waste become composite board with economic value.